Quasi‐Zero Volume Strain Cathode Materials for Sodium Ion Battery through Synergetic Substitution Effect of Li and Mg - Shen, Ming‐Yuan; Wang, Jing‐Song; Ren, Zhouhong; Wu, Tao; Liu, Xi; Chen, Liwei; Li, Wen‐Cui; Lu, An‐Hui (Advanced functional materials, 2023)
P2‐type layered oxide material Na 2/3 Ni 1/3 Mn 2/3 O 2 is a competitive candidate for sodium‐ion batteries (SIBs). Nevertheless, it suffers from the strong P2–O2 phase transition during charging to the high voltage regime, rendering drastic volume variations and poor cycling performance. Here, a Quasi‐zero strain P2‐Na 0.75 Li 0.15 Mg 0.05 Ni 0.1 Mn 0.7 O 2 cathode is synthesized, which reflects the vanishing P2–O2 transition with a volume change as low as 0.49%, thus resulting in the material an excellent cycling performance (83.9% capacity retention after 500 cycles at 5 C). The low‐volume strain can be attributed to two aspects: (1) the Mg 2+ riveted in the Na layer can act as a “pillar” to stabilize the crystal structure under the condition of sodium removal, thus restricting the structural changes under high voltage. (2) The entry of Li + into the transition metal (TM) layer can mitigate the electron localization in the highly desodiation state and can effectively immobilize the coordination oxygen atoms, thus suppressing the slip of P2–O2 transition. This study not only provides a new insight of Li and Mg synergetic substitution effect on the structural stability of P2‐type cathode, but also an efficient avenue for developing cathode materials of SIBs with ultralow bulk strain.